APPEARANCE OF BROILER THAT IS GIVEN DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER - N. W. R., Maheri; Candrawati, D. P. M. A.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the effect of giving dragon peel fruit juice through drinking water on the appearance of broiler that have been carried out in Buahan Village, Penebel District, District Tabanan for 5 weeks. This study used a Completely Randomized Design (CRD) consisting of four treatments , fur replicates and each replication consisted of four chickens . The treatments given were broilers given drinking water without dragon fruit peel juice (P0), broilers who were given 2% dragon fruit peel juice in drinking water (P1), broilers who were given 4 % juice peel dragon fruit in drinking water (P2), and broilers who were given 6% % juice peel dragon fruit in drinking water (P3). The variables observed included ration consumption, drinking water consumption, final body weight, weight gain and FCR. The results of this study showed that ration consumption and drinking water consumption were not significantly different (P>0.05) higher than broiler chickens that received P0 treatment. The final body weight of P2 and P3 treatments was significantly (P<0.05) higher than the chickens that received P0 and P1 treatments. The increase in body weight of broiler chickens that received P1, P2, and P3 treatments was significantly higher (P<0.05) higher than P0 treatment, while the FCR values of the four treatments were not significantly different (P>0.05). Based on the results of this study it was concluded that Giving juice peel dragon fruit in drinking water could same increase ration consumption, drinking water consumption, and FCR value while giving juice peel dragon fruit in drinking water at a level of 2%-6% was able to increase final body weight and able weight gain. Keywords: Skin Juice Fruit Dragon, Broiler, Performance